2018
DOI: 10.1016/j.injury.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Definition of infection after fracture fixation: A systematic review of randomized controlled trials to evaluate current practice

Abstract: This systematic review shows that IAFF is not defined in a large majority of the fracture-related literature. To our knowledge, this is the first study conducted with the objective to explore this important issue. The lack of a consensus definition remains a problem in current orthopedic trauma research and treatment and this void should be addressed in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 99 publications
2
51
0
1
Order By: Relevance
“…Furthermore, only one study used a standardized definition for FRI (e.g., CDC guidelines) out of 47 studies using a definition. This is in line with conclusions of a previous review of 100 randomized clinical trials aimed at defining FRI [103]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, only one study used a standardized definition for FRI (e.g., CDC guidelines) out of 47 studies using a definition. This is in line with conclusions of a previous review of 100 randomized clinical trials aimed at defining FRI [103]. …”
Section: Discussionsupporting
confidence: 92%
“…Due to heterogeneity it is almost impossible to compare outcome between studies. One explanation for this wide variety of published treatment strategies could be the lack of a consensus in the orthopedic trauma community regarding these strategies to manage FRI [103]. …”
Section: Discussionmentioning
confidence: 99%
“…a 6 week transition from acute to chronic infection). All these concerns pose serious problems from a definition point of view [3]. Of course, the participants did agree that acute and chronic infections are different entities that may require different treatment strategies; however, it should not impact upon the way clinicians define FRI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this issue was previously raised in an AO/ASIF scientific supplement publication by Arens et al in 1996, wherein the authors stated in a combined clinical and experimental study on FRI: 'It is astonishing that in all papers in which infection is mentioned, the term 'infection' is not defined' [2]. In fact, this was confirmed by a recent systematic review, which showed that only a minority of randomized controlled trials (2%) in fracture care use any kind of standardized definition of infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…We sometimes use the CDC guideline to prevent surgical-site infection (SSI), which distinguishes between superficial incisional, deep incisional and organ/space infections [13]. However, this guideline was not specifically developed for fracture patients [16], and for this reason, the term SSI is used in this review for lack of a clear alternate definition, although the authors are aware of the need for a consensus definition of FRI [18].…”
Section: Definitionmentioning
confidence: 99%